Combination of peptides with biological, organic, and inorganic materials for synergistically enhanced diagnostics and therapeutics. Issue 3 (26th May 2021) - Kim, Joo‐Young; Lee, Jae Yun; Park, Ha Yeon; Kim, Hyunji; Kang, Jeon Hyeong; Kim, Hyun Jin; Jeong, Woo‐Jin
Abstract: Armed with the useful properties of small molecules and proteins, peptides hold the potential to be utilized in almost all biomedical research fields. However, the clinical application of peptides has been limited due to their intrinsic drawbacks, such as poor plasma stability and low target binding affinity. The conjugation of peptides to biological, organic (nonbiological), and inorganic materials has recently emerged as a promising strategy to address these problems. Hence, in this article, we provide an overview of the successful outcomes of using peptide‐bio/organic/inorganic conjugates in various biomedical applications, including the diagnosis and treatment of diseases. Abstract :